A Method Suitable for Predicting the Crystal Densities of Cyclic Organic Fluorides. Issue 6 (10th February 2020) - Wang, Guixiang; Zhang, Wenjing; Liu, Yan; Gao, Pin; Gong, Xuedong
Abstract: Crystal density is a basic and important parameter for predicting the detonation performance of explosives. In this study, the densities of 35 cyclic organic fluorides, a kind of compounds with wide applications, are investigated using three density functionals (B3LYP, B3PW91, M06‐2X) and six basis sets (such as 6–31G*, 6–31+G* and 6–31G**) via two approaches (A and B). Compared with the experimental results, the calculated densities by various methods are all overestimated. However, the densities obtained by M06‐2X/6‐31G* via the approach A show a good linear correlation with the experimental values, therefore, they can be systematically corrected using the correlation equation to reproduce the experimental crystal densities satisfactorily. In addition, the effects of various groups (−NO2, −CH2 −, −CF(NO2 )2, −CNF2 (NO2 )2, −CF3, −SF5, and −NF2 ) on the densities of organic fluorides, which is helpful for the design of new fluorine‐containing molecules in terms of requirement, have also been discussed. Abstract : Crystal density is a basic and important parameter for predicting the detonation performance of explosives. The densities of 35 cyclic organic fluorides, a kind of compounds with wide applications, are investigated using three density functionals (B3LYP, B3PW91, M06‐2X). Compared with the experimental results, it is found that the M06‐2X/6‐31G* method gives satisfactory results with a root mean square deviation of 0.05 cm −3 . So it is a suitable method for predicting the crystal densities of cyclic organic fluorides.